RABITA MODEL SCHOOLS MANAGEMENT SYSTEM - Tamimi, Abdel-Raheem; Jabari, Anan; Salaymeh, Fathi (جامعة بوليتكنك فلسطين - تكتنولوجيا المعلومات)
This system is a database application that runs over the web through the intranet of al Rabita model school, which aims to computerize and manage some of the processes that are related to the School, these processes include the student accumulative card, marks and certifications, accounting issues and school affairs. This system allows the user of the system storing and managing information about the students of the school in a very simple way. The system also allows the user to manage the sections of the classes, and to store the marks of the students and to manage them, and then he can either ask the system to store the certificates – including the school certificates and the Ministry of education standard sheet- or to print them out. Also the system considers managing the accounting processes that are related to the school such as the school tuitions and transportation subscription fees by calculating the required fees from the parents taking in mind the discount processes for the brothers and superior students. In addition the system will provide the user with the needed reports and certificates such as recommendation letters and certifications. This report describes the development life cycle for this system starting from the system specifications, going through the system functional specifications, system design, system implementation, system testing and finally the system maintenance.
CD, 17497 , 15/2004 تكنولوجيا المعلومات , no of pages 154
Keywords: MANAGEMENT SYSTEMS - RABITA MODEL SCHOOLS